Research Progress on the Immune Function of Liver Sinusoidal Endothelial Cells in Sepsis - Xinrui Wang; Zhe Guo; Yuxiang Xia; Xuesong Wang; Zhong Wang (Cells, 2025)
Sepsis is a complex clinical syndrome closely associated with the occurrence of acute organ dysfunction and is often characterized by high mortality. Due to the rapid progression of sepsis, early diagnosis and intervention are crucial. Recent research has focused on exploring the pathological response involved in the process of sepsis. Liver sinusoidal endothelial cells (LSECs) are a special type of endothelial cell and an important component of liver non-parenchymal cells. Unlike general endothelial cells, which mainly provide a barrier function within the body, LSECs also have important functions in the clearance and regulation of the immune response. LSECs are not only vital antigen-presenting cells (APCs) in the immune system but also play a significant role in the development of infectious diseases and tumors through their specific immune regulatory pathways. However, in certain disease states, the functions of LSECs may be impaired, leading to immune imbalance and the development of organ failure. Investigating the immune pathways of LSECs in sepsis may provide new solutions for the prevention and treatment of sepsis and is crucial for maintaining microcirculation and improving patient outcomes.